The Relationship between The Characteristics of Type 2 Diabetes Mellitus Patients and The Chronic Kidney Disease Stage during The COVID-19 Pandemic at RSI Jemursari Surabaya - Irawan, Danny; Effendi; Donastin, Adyan; Agustiandani, Rifka Windi; Tsabita, Andhien Syifa’; Iryawan, Rifky Dwi Aditya; Oktaviana, Betta Mega; Muhammad, Akbar Reza (UNUSA Press, 2024)
Introduction: The prevalence of diabetes mellitus has risen globally, posing a substantial health challenge, with a marked increase reported in both developed and developing nations. Diabetes is a primary contributor to the global prevalence of Chronic Kidney Disease (CKD). During the pandemic, there is a considerable challenge, especially for CKD patients, including a loss in health services, vulnerability to COVID-19 infection, stressful events during social distancing, and a decrease in therapy adherence. Hence, the COVID-19 pandemic may give rise to various characteristics in individuals with chronic kidney disease. Objective: To investigate the correlation between the characteristic of patients with type 2 diabetes mellitus and the chronic kidney disease (CKD) stage at RSI Jemursari Surabaya during the COVID-19 pandemic. Methods: An observational analytical cross-sectional study was conducted on individuals with chronic kidney disease (CKD) previously diagnosed with diabetes mellitus (DM) during the COVID-19 pandemic from 2020 to 2022. A total of 169 samples were obtained using a simple random sampling method. The variables considered include age, gender, HbA1c, blood pressure, cardiovascular comorbidities, Pulmonary comorbidities, and history of COVID-19. Results: The study demonstrated a significant correlation between blood pressure and kidney function tests, including blood creatine level, BUN, and eGFR, with CKD stage (P<0.05). Randomised blood glucose also has a significant correlation to the CKD stage. No notable correlation was observed among age, gender, HbA1c levels, cardiovascular comorbidities, pulmonary comorbidities, and history of COVID-19. Conclusions: The presence of hypertension and abnormal kidney function test results correlate with the stage of chronic kidney disease (CKD) during a pandemic.